How should we 'care' for LGBT+ students within higher education?. (3rd July 2017) - Formby, Eleanor
Abstract: This article draws on a recent U.K. research project about lesbian, gay, bisexual and trans (LGBT+) perspectives on university to examine the implications for pastoral care and other service provision on campus. In a departure from previous scholarship that has tended to understand LGBT+ students as 'vulnerable' and/or needing 'support', it argues that university spaces should be (re)framed in a way that moves beyond (only) personal or individual 'care'. The article outlines some of the issues that LGBT+ students may face under the following headings: Curriculum and course content; Discrimination, prejudice and bullying; Facilities and service provision on campus; A continuum of experiences. Following these, a final section draws some conclusions and implications for practice in higher education.